PENGEMBANGAN KOMPETENSI GURU MELALUI SEMINAR METODE DAN MEDIA PEMBELAJARAN PAI DI MADRASAH DINIYAH AL-IHYA KECAMATAN BOGOR BARAT, KOTA BOGOR - Fauziah, Ratu Dinny; Muhammad Rizal (Universitas Nusa Bangsa, 2024)
The development of learning methods and media is very important in learning in schools or madrasas, learning will be said to be effective if you choose the right learning methods and media because it can facilitate teaching and learning activities, especially in learning Islamic Religious Education so that learning objectives are achieved. To improve competence in learning at Madrasah Diniyah Al Ihya, our team of lecturers from STIT Insan Kamil Bogor provides abdimas counseling activities on the development of PAI learning methods and media, as alternative solutions to existing problems. The purpose of this community service activity is to provide counseling regarding alternatives to several learning models and after understanding the various models and learning methods presented, Madrasah Diniyah Al Ihya teachers are expected to be able to teach with various alternative methods so that learning objectives can be achieved if problems occur, especially regarding interests and student interest. The research method used is a qualitative method, namely by collecting data in the form of surveys, direct observations and counseling. The results of this study are the increasing competence of educators in the form of knowledge and understanding of the Majlis Al-Ihya congregation in the development of PAI learning methods and the skills of the congregation in developing PAI learning methods are increasing. Keywords: Islamic Religious Education, methods, learning media Abstrak Pengembangan metode dan media pembelajaran sangatlah penting dilakukan dalam suatu pembelajaran di sekolah maupun madrasah. Pembelajaran dinyatakan efektif jika penggunaan metode dan media pembelajaran yang digunakan sesuai untuk mata pelajaran Pendidikan Agama Islam (PAI), sehingga tujuan pembelajaran akan tercapai. Tim dosen STIT Insan Kamil Bogor telah memberikan kegiatan seminar abdimas tentang pengembangan kompetensi guru melalui seminar metode dan media pembelajaran PAI dengan tujuan para pengajar dapat meningkatkan kompetensi pembelajaran di Madrasah Diniyah Al Ihya untuk mengatasi permasalahan mengenai minat dan ketertarikan anak didik. Pada kegiatan pengabdian kepada masyarakat di Madrasah Diniyah Al Ihya menggunakan metode kualitatif dengan cara mengumpulkan data berupa survei, pengamatan langsung dan seminar. Pada kegiatan pengabdian kepada masyarakat ini, hasil pengamatan melalui metode survei yang dilakukan oleh pelaku kegiatan menunjukkan hasil dengan bertambahnya pengetahuan dan meningkatnya kompetensi pendidik berupa pemahaman dalam pengembangan metode pembelajaran PAI, sehingga metode dan media pembelajaran ini efektif untuk digunakan di pembelajaran khususnya di Madrasah Diniyah Al Ihya. Kata Kunci: Pendidikan Agama Islam (PAI), metode, media pembelajaran